2009
DOI: 10.1002/jclp.20610
|View full text |Cite
|
Sign up to set email alerts
|

Partnering with families: multiple family group psychoeducation for schizophrenia

Abstract: Family psychoeducation (FPE) is one of six evidence-based practices endorsed by the Center for Mental Health Services for individuals suffering from chronic mental illnesses. Multiple family group psychoeducation (MFG) has been shown to be an effective component of FPE in reducing symptom relapses and rehospitalizations for individuals with schizophrenia. It is especially effective when family members participate on a consistent basis, which allows them to increase their understanding of the biology of the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 14 publications
2
47
0
3
Order By: Relevance
“…Multiple family group psychoeducation (MFG) has been shown to be an effective component of family psychoeducation (FPE) in reducing symptom relapses and rehospitalizations for individuals with schizophrenia 80 . It is especially effective when family members participate on a consistent basis, which allows them to increase their understanding of the biology of the disorder, learn ways to be supportive, reduce stress in the environment and in their own lives, and develop a broader social network.…”
Section: Results Of Psychoeducational Programsmentioning
confidence: 99%
“…Multiple family group psychoeducation (MFG) has been shown to be an effective component of family psychoeducation (FPE) in reducing symptom relapses and rehospitalizations for individuals with schizophrenia 80 . It is especially effective when family members participate on a consistent basis, which allows them to increase their understanding of the biology of the disorder, learn ways to be supportive, reduce stress in the environment and in their own lives, and develop a broader social network.…”
Section: Results Of Psychoeducational Programsmentioning
confidence: 99%
“…I conducted this research in the context of an intervention study of family psychoeducation that I previously developed and pilot-tested as an ethnic-sensitive program for Chinese Americans ( Kung, Tseng, Wang, Hsu, & Chen, 2012). Family psychoeducation has been proven effective in reducing caregiver stress and the relapse rate of individuals with schizophrenia ( Jewell, Downing, & McFarlane, 2009;Lefley, 2010;McFarlane, Dixon, Lukens, & Lucksted, 2003). The intervention protocols focus on educating the families about the nature of the illness, promoting better communication, and helping family members resolve conflicts ( Anderson, Reiss, & Hogarty, 1986;McFarlane, 2002) to reduce "expressed emotions" such as criticism and overinvolvement, which highly predict relapses ( Butzlaff & Hooley, 1998;Hooley, 2007;Leff & Vaughn, 1985;Marom, Munitz, Jones, Weizman, & Hermesh, 2005).…”
mentioning
confidence: 99%
“…Social function and social support in families can have many effects on people's mental disorders or mental health (20). The results of Jewell et al (2009) study showed that family's psychological education is effective in controlling stress and worries and improving the mental, social, and functional health of schizophrenic patients and their families (21). Fristad (2003) believed that psychological training of the family could increase the survival rate of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the Kwan study (2004) in Germany showed that social support and family performance are effective in the mental health of patients (20). The results of Jewell et al (2009) showed that family's psychological education in controlling stress and concern is effective in improving mental health (21). Fristad (2003) believed that family's psychological education could increase the mental health endurance in patients (22).…”
Section: Introductionmentioning
confidence: 99%